Probable mechanisms of biocidal action of Cocos nucifera Husk extract and fractions on bacteria isolates - Akinpelu, David A; Alayande, Kazeem A; Aiyegoro, Olayinka A; Akinpelu, Oluseun; Okoh, Anthony (BMC complementary and Alternative Medicine, 2020)
International Journal of BMC Complementary and Alternative Medicine